872 Disruption of KIF3a Increases Sensitivity of Primary Glioblastoma Cells to Temozolomide and Radiotherapy. (April 2023) - Kaculini, Christian; Springer, Megan; Jung, Mi-Yeon; Brown, Desmond A.
Abstract : INTRODUCTION: Glioblastoma (GBM) is the most common primary malignant brain tumor, comprising 14.3% of all intracranial neoplasms and 49.1% of all malignant brain tumors. The current standard of care for newly diagnosed glioblastoma is maximal safe resection, 60 Gy of radiotherapy over a 6-week period, plus concomitant daily temozolomide, followed by adjuvant temozolomide over 6 months. Nonetheless, median overall and 5-year survival are only 15 months and 5%, respectively. Primary cilia are microtubule-based organelles that protrude from the apical surface of nearly all mammalian cells. They are critical to many canonical signaling pathways and are closely related to the cell cycle. They have been implicated in the formation and progression of many malignancies and are associated with resistance to chemoradiotherapy. METHODS: Patient-derived GBM cell lines were transduced with lentiviral particles to produce stable cell lines deficient in proteins essential for primary cilia regulation. Cell proliferation assays were used to assess sensitivity of each knockdown to temozolomide and radiotherapy. RESULTS: Proliferation of KIF3A knockdown cells was significantly decreased compared to control lines after radiotherapy (P = 0.009). GBM cells with disrupted primary cilia were more frequently found in the G2/M phase potentially explaining the increase in sensitivity. KIF3A depleted cells also displayed improved response to temozolomide. MGMT protein expression was decreased in these cells, providing a potential mechanism for the decrease in proliferation. This finding reveals a new relationship between primary cilia and MGMT, an extremely important biomarker that is commonly used to predict the efficacy of alkylating chemotherapy. CONCLUSIONS: Collectively, our findings provide strong evidence that primary cilia play an important role in resistance to the current standard treatment of GBM and identify KIF3A as a potential sensitizer to chemoradiation in GBM.